Attitude of Faculty Members of Tehran Universities towards the Cultural Activities of the Faculty Members Based on the New Regulations for the Faculty Members' Promotion - Jalil fathabadi (Taḥqīqāt-i Farhangī-i Īrān, 2014)
The main objective of the present research the exploration Tehran University's faculty views about new regulations promotion and add a material change in activities of cultural - educational - social. The method of this research is mixed method, that quantitative phase of the type of survey. The sample in qualitative phase include 34 individuals and quantitative phase include 250 of faculty members from six Universities of Tehran, Shahid Beheshti, Kharazmi, Tarbiat Modares, Alameh-Tabatabai, and Sharif that in qualitative phase by using convenient sampling and in quantitative phase by using purposive sampling Were selected. To do research on the qualitative phase of semi-structured interviews and 8 open-ended questions and in quantitative phase questionnaire consisting of 35 questions and 3 sections: 1. Views and opinions 2. Operational issues, and 3. Suggestions have been used. In general we can say that faculty members to the necessity of its faculty and universities cultural issues they believe, However, these activities should be done by whom and in what manner, how should be evaluated together and with Cultural Affairs in Higher Education planners have differences in opinion. In the opinion of faculty members, the perspective of cultural and educational activities, as well as faculty teaching and research and opinion latent within the many cultural activities in education and training is indivisible.